PEMANFAATAN APLIKASI UTM GEO MAP DALAM PEMBELAJARAN FISIKA UNTUK MEMAHAMI KONSEP KELERENGAN - Fitrianingrum, Aufa Maulida; Kurniahtunnisa; Nggolaon, Delpina (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
This study aims to explore the use of the UTM Geo Map application as a physics learning media to understand the concept of slope. The research uses a qualitative approach with subjects being students from the S1 Science Education Study Program at Universitas Negeri Manado for the 2023/2024 academic year. The research consists of five stages: planning, application usage practice, data collection, data analysis, and conclusion drawing. The study shows that the slope analysis between two coordinate points in Universitas Negeri Manado, 1.2666026° N, 124.8826783° E and 1.2730803° N, 124.8904382° E, results in an angle of 3.62°, categorized as a gentle slope. The practice of utilizing UTM Geo Map helps students relate physics theory, particularly the concept of inclined planes, to real geographical phenomena encountered in their surrounding environment. Students can also create contour lines, identify elevations, and observe topographic shapes directly through the application’s features. Student feedback indicates that the learning process becomes more contextual, engaging, and meaningful. The use of geospatial-based technology provides an effective alternative to enrich learning experiences, especially in physics education that requires real visualization of spatial and field concepts.